Dynamics of gut microbiota in patients suffering from hematologic malignancies after allogeneic hematopoietic stem cell transplantation - Akhremchuk, Katsiaryna V.; Skapavets, Katsiaryna Y.; Akhremchuk, Artur E.; Kirsanava, Natallia; Sidarenka, Anastasiya V.; Valentovich, Leonid N. (Experimental Biology and Biotechnology, 2022)
In this study, we described the dynamics of intestinal microbiota of 32 patients after allogeneic hematopoietic stem cell transplantation (HSCT). After HSCT, on 14th day and 30th day, the inverse Simpson index value was more than 3 times lower compared to the pre-HSCT period. Biodiversity became more similar to the pre-HSCT level by 100th day. The correlation between diversity of microbiota and development of post-HSCT complications wasn’t observed. Our findings indicated individual-specific changes in the taxonomic structure of patients’ microbiota after HSCT. Changes in the relative abundance of the bacterial families Streptococcaceae, Actinomycetaceae, Acidaminococcaceae, Akkermansiaceae, Desulfovibrionaceae, Prevotellaceae, genera Streptococcus, Clostridioides, Phascolarctobacterium, Paraprevotella, Bilophila, Akkermansia, Coprococcus, Sutterella, Alistipes appear to be associated with the development of post-HSCT complications. High abundance of phylum Proteobacteria, families Actinomycetaceae and Streptococcaceae, genus Streptococcus before HSCT can be considered as a potential predictor of graft-versus-host disease development in the post-HSCT period.
Keywords: microbiome; graft-versus-host disease; dysbiosis; metagenomics